Survivor song : a novel - Tremblay, Paul (New York : William Morrow, 2020)
In a matter of weeks, Massachusetts has been overrun by an insidious rabies-like virus that is spread by saliva. But unlike rabies, the disease has a terrifyingly short incubation period of an hour or less. Those infected quickly lose their minds and are driven to bite and infect as many others as they can before they inevitably succumb. Hospitals are inundated with the sick and dying, and hysteria has taken hold.
Keywords: Virus diseases -- Fiction; Pregnant women -- Fiction; Survival -- Fiction; Massachusetts -- Fiction; Horror fiction; Thrillers (Fiction); Psychological fiction